2015
DOI: 10.4067/s0034-98872015000900003
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de la injuria renal aguda en unidad de paciente crítico y su mortalidad a 30 días y un año

Abstract: Incidence and consequences of acute kidney injury among patients admitted to critical care units (Rev Med Chile 2015; 143: 1114-1120

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(56 reference statements)
0
4
0
2
Order By: Relevance
“…This rate agrees with rates found nationally and internationally. (13)(14)(15)(16) After define sociodemographic and clinical profile of patients, we observed prevalent diagnoses, most common were: risk of infection, risk of inefficient gastrointestinal perfusion, risk of inefficient renal perfusion, excessive fluid volume, risk of electrolytic imbalance, risk of imbalance fluid volume. These results are similar to other Brazilian studies that used Delphi's technique and identified five main diagnosis: decreased cardiac output, inefficient tissue perfusion -renal, impaired fluid volume, excessive fluid volume, and risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This rate agrees with rates found nationally and internationally. (13)(14)(15)(16) After define sociodemographic and clinical profile of patients, we observed prevalent diagnoses, most common were: risk of infection, risk of inefficient gastrointestinal perfusion, risk of inefficient renal perfusion, excessive fluid volume, risk of electrolytic imbalance, risk of imbalance fluid volume. These results are similar to other Brazilian studies that used Delphi's technique and identified five main diagnosis: decreased cardiac output, inefficient tissue perfusion -renal, impaired fluid volume, excessive fluid volume, and risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality also varies widely, ranging from 15 to 60% depending on the associated diseases [ 6 , 7 ]. Approximately 30% of patients discharged from the ICU that required RRT will remain in the most advanced stage of chronic kidney disease (CKD-5) [ 7 – 9 ], which could be related to a lower long-term survival [ 10 12 ]. Different studies have established risk factors at the individual level that determine prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Este tipo de injuria ocurre en aproximadamente el 5 al 25% de los pacientes en la Unidad de Paciente Crítico (UPC) en la mayoría de las series, pero puede llegar hasta 70% dependiendo de la población estudiada (2)(3)(4)(5) . En Chile, se estima que puede llegar hasta el 28,9% (6) . De todos esos pacientes, entre el 5 al 50% van a requerir terapia de reemplazo renal (TRR) (2,3,5) y entre el 70 al 80% se inicia terapia de reemplazo renal continua (TRRC) (7) por su estabilidad hemodinámica y control de solutos (8) .…”
Section: Introductionunclassified